Main Character Syndrome: Manifestations and Impact on Social - Tasya, Amalia (PT. Anagata Sembagi Education, 2025)
Main Character Syndrome (MCS) is a psychological phenomenon in which individuals tend to see themselves as the main characters in life, often in an exaggerated and dramatic manner. In the era of social media, this phenomenon is increasingly prevalent, influenced by digital algorithms that reinforce narcissistic mindsets and the search for social validation. This article examines various manifestations of MCS in social interactions and their impact on interpersonal relationships. Using qualitative methods based on literature analysis, this study found that MCS can enhance self-expression but also trigger problems in empathy and social connectedness. Therefore, it is important to understand the balance between individuality and social awareness in everyday life.